2001
DOI: 10.1007/s004280000368
|View full text |Cite
|
Sign up to set email alerts
|

p16 Alterations and retinoblastoma protein expression in squamous cell carcinoma and neighboring dysplasia from the upper aerodigestive tract

Abstract: The progression potential of preinvasive epithelial lesions is usually evaluated by assessing the degree of histologic dysplasia. We examined p16, retinoblastoma protein (pRb), and proliferating cell nuclear antigen (PCNA) immunophenotypes in 57 cases of previously untreated squamous cell carcinoma (SCC) of the upper digestive tract and in the neighboring normal and dysplastic epithelia. Tissue samples were examined for homozygous deletion of exon 2 of the p16 gene using polymerase chain reaction (PCR) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
3
22
0
1
Order By: Relevance
“…In addition, mdm2 protein is expressed in HNSCC mostly at advanced stages (Ambrosch and Ruschenburg, 2000). Therefore, it is conceivable that these are not relevant targets in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mdm2 protein is expressed in HNSCC mostly at advanced stages (Ambrosch and Ruschenburg, 2000). Therefore, it is conceivable that these are not relevant targets in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported p16 protein inactivation, resulting from either gene deletion or promoter methylation, in oral cancers (79), esophageal squamous carcinomas (51), upper aerodigestive tract (59), and head and neck squamous carcinomas (80). In control mice, most p16-stained cells were in the basal layer of the tongue epithelium, whereas in invasive carcinomas of the tongue, only a few cells showed p16 staining (Fig.…”
Section: The Effects Of 4-nqo On Cell Growth and Cell Cycle Regulatormentioning
confidence: 99%
“…p16 is a target commonly involved in esophageal carcinogenesis (51), and the abrogation of p16 occurs frequently in human oral cancers (52). The loss of expression of p16 has been observed in oral premalignant lesions (53,54), primary tumors of the oral cavity (55)(56)(57)(58), and squamous carcinomas of the upper aerodigestive tract (59).…”
Section: The Expression Of P16 Was Decreased In the Epithelia Of Mousmentioning
confidence: 99%
“…Gonzales et al [29] also found association between p16 expression and inflammatory cells. The loss of function of pRB due to mutations or chromosomal deletions may also result in high expression of p16; however, loss of pRB function in the head and neck occurs in a small number of tumors [42].…”
Section: Discussionmentioning
confidence: 99%